Effects of Papaya (Carica Papaya) Leaf Extract on Collagen Synthesis Enhancement in Various Experimental Studies: Molecular and Histological Review - Kristanto, Andre; Satriyasa, Bagus Komang; Artini , I Gusti Ayu (CV. Publikasi Indonesia, 2025)
Collagen synthesis plays an important role in tissue regeneration and the skin aging process. This process can be disrupted by oxidative stress as well as increased expression of matrix metalloproteinases (MMPs). Papaya (Carica papaya L.) leaf extract contains bioactive compounds such as quercetin, vitamin C, and papain, which have the potential to stimulate collagen synthesis. The aim of this review was to analyze experimental evidence related to the effects of papaya leaf extract on collagen synthesis through molecular and histological approaches. Literature searches were conducted through PubMed, Google Scholar, and MDPI databases using the keywords “papaya leaf extract,” Carica papaya, “collagen,” and “photoaging.” Five articles that met the inclusion criteria were analyzed. Papaya leaf extract has been shown to lower ROS levels, suppress MMP expression, and activate the TGF-β pathway. Histological results demonstrated increased expression of type I collagen and accelerated wound healing in animal models. The potential of papaya leaf extract as a topical anti-aging agent and regenerative therapy is considered promising. However, further research is needed to determine the optimal dose and evaluate long-term safety.